Characterization of Recombinant Chimpanzee Adenovirus C68 Low and High-Density Particles: Impact on Determination of Viral Particle Titer - Mullins, Elise K.; Powers, Thomas W.; Zobel, Jim; Clawson, Kory M.; Barnes, Lauren F.; Draper, Benjamin E.; Zou, Qin; Binder, Joseph J.; Dai, Stanley; Zhang, Kun; Friese, Olga; Runnels, Herbert A.; et al. (Frontiers in Bioengineering and Biotechnology, 2021)
We observed differential infectivity and product yield between two recombinant chimpanzee adenovirus C68 constructs whose primary difference was genome length. To determine a possible reason for this outcome, we characterized the proportion and composition of the empty and packaged capsids. Both analytical ultracentrifugation (AUC) and differential centrifugation sedimentation (DCS, a rapid and quantitative method for measuring adenoviral packaging variants) were employed for an initial assessment of genome packaging and showed multiple species whose abundance deviated between the virus builds but not manufacturing campaigns. Identity of the packaging variants was confirmed by charge detection mass spectrometry (CDMS), the first known application of this technique to analyze adenovirus. The empty and packaged capsid populations were separated via preparative ultracentrifugation and then combined into a series of mixtures. These mixtures showed the oft-utilized denaturing A260 adenoviral particle titer method will underestimate the actual particle titer by as much as three-fold depending on the empty/full ratio. In contrast, liquid chromatography with fluorescence detection proves to be a superior viral particle titer methodology.